2018
DOI: 10.14202/vetworld.2018.868-873
|View full text |Cite
|
Sign up to set email alerts
|

Extended-spectrum β-lactamases producing multidrug resistance Escherichia coli, Salmonella and Klebsiella pneumoniae in pig population of Assam and Meghalaya, India

Abstract: Aim:The present study was conducted to record the prevalence of extended spectrum β-lactamases (ESBLs) producing Escherichia coli, Salmonella spp., and Klebsiella pneumoniae from pig population of Assam and Meghalaya and to record the ability of the resistant bacteria to transfer the resistance genes horizontally.Materials and Methods:Fecal samples (n=228), collected from pigs of Assam (n=99) and Meghalaya (n=129), were processed for isolation and identification of E. coli and Salmonella spp. All the isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…In India, Lalruatdiki et al [14] observed that 30% of Salmonella isolated from a pig population were carrying bla TEM , and 10% were carrying bla CTX−M . Co-carriage of bla CTX−M and bla TEM has also been observed in extended-spectrum ß-lactamase (ESBL)-producing Salmonella from pigs [14,29]. In the present study, co-carriage of bla TEM and bla CTX−M was found in seven (3.9%) isolates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In India, Lalruatdiki et al [14] observed that 30% of Salmonella isolated from a pig population were carrying bla TEM , and 10% were carrying bla CTX−M . Co-carriage of bla CTX−M and bla TEM has also been observed in extended-spectrum ß-lactamase (ESBL)-producing Salmonella from pigs [14,29]. In the present study, co-carriage of bla TEM and bla CTX−M was found in seven (3.9%) isolates.…”
Section: Discussionmentioning
confidence: 99%
“…These genes are broadly distributed worldwide and are commonly found in association with genes encoding for ß-lactamases [8][9][10][11]. Consequently, bla and qnr genes have been increasingly found in bacteria isolated from livestock animals [8,9,[12][13][14][15][16][17]. If motile, resistance determinants may accelerate the spread of AMR when these are taken up by non-pathogenic or pathogenic bacteria alike.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Lalruatdiki et al . [ 15 ] could recover 867 E. coli from 228 fecal samples from pigs of Meghalaya and Assam. On the other hand, Samanta et al .…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, from the same laboratory, Lalzampuia et al [11] isolated 102 E. coli from 53 fecal samples from pigs in Mizoram. On the other hand, Lalruatdiki et al [15] could recover 867 E. coli from 228 fecal samples from pigs of Meghalaya and Assam. On the other hand, Samanta et al [16] reported only 76 E. coli from 200 fecal samples in West Bengal, India.…”
Section: Discussionmentioning
confidence: 99%
“…The use of critically important human antibiotics in farm animals is leading the emergence of new Multi Drug Resistant (MDR) bacteria (Lalruatdiki, Dutta, Roychoudhury, & Subudhi, ). MDR K. pneumoniae strains have been isolated from fresh raw seafood, fresh raw chicken, frozen raw food, and cooked food samples like meat, vegetables, rice products (Guo et al, ), marketed fresh vegetables (Falomir, Rico, & Gozalbo, ), shrimp in international trade (Nawaz et al, ), and farm‐raised chicken (Wu et al, ).…”
Section: Introductionmentioning
confidence: 99%